Constitutional engineering in a presidential Colombia: History of an error in the construction of the Public Ministry and its faculty of disciplinary control - Zarabanda Suárez, Diana Marcela (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Sartori’s constitutional engineering raises the need to analyze the construction of legal-political institutions through a technique of incentives and punishments. The present paper investigates the existence or not of incentives to direct the power of disciplinary control by the Attorney General’s Office against the president and his ministers as a result of a passive legislative power in that activity due to a presidential regime that mixes the agendas of Congress and the President. The result of this study shows a gross error in the deployment of constitutional engineering that made the control of the Public Ministry over the Government insipient.